The Surface Geology and Geomorphology Around Gobabeb, Namib Desert, Namibia. Issue 4 (17th October 2013) - Eckardt, Frank D.; Livingstone, Ian; Seely, Mary; Von Holdt, Johanna
Abstract This paper serves as a brief review and overview of the surface geology and geomorphology around Gobabeb in the Central Namib Desert. It introduces the major lithologies associated with the Damara Orogen of Precambrian and Cambrian age, followed by Tertiary sandstones and conglomerates and Quaternary Kuiseb valley conglomerates, silts and gravels. To celebrate the 50th anniversary of the Gobabeb research station and the recent designation of the Namib Sand Sea as a world heritage site, we are presenting a map to inform and guide future research and educational activities around Gobabeb. The contrast between an ancient gravel plain to the north, a dynamic aeolian sand sea to the south and ephemeral river environments in between become apparent. These natural laboratories have attracted investigations of contemporary sand dune movement, hyper saline waters, evaporites and duricrusts and ephemeral flooding and recharge processes as well as environmental change and human impacts.